Consensus of Fractional-Order Multiagent Systems with Double Integrator under Switching Topologies. (16th August 2017) - Shen, Shiyun; Li, Wenjing; Zhu, Wei
Abstract : Due to the complexity of the practical environments, many systems can only be described with the fractional-order dynamics. In this paper, the consensus of fractional-order multiagent systems with double integrator under switching topologies is investigated. By applying Mittag-Leffler function, Laplace transform, and dwell time technique, a sufficient condition on consensus is obtained. Finally, a numerical simulation is presented to illustrate the effectiveness of the theoretical result.